PERAN JURNALISME WARGA (CITIZEN JOURNALISM) BERBASIS SANTRI SEBAGAI PENYEIMBANG KOMUNIKASI KEAGAMAAN LOKAL KEDIRI - Diah Handayani (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2017)
The aim of this research is to improve awareness of the religious multivarians local information that constructed by the Pesantren. Improving the dakwah Pesantren by constructed the santri capacity improving the santri skills to conduct the news, features, public opinion, and the articles by citizen journalism. And the process of social construction of santri about radicalism of pesantren, according to four stages of social construction of mass media by Burhan Bungin; phase of construction materials prepare, phase of construction distribution, materials construction formation, and phase of confirmation. This research based on qualitative research method. Explaining and answering the questions of “why” and “how” of the research focus in this case study in The Hidayatul Mubtadi’ien Lirboyo Pesantren. This research used data from interview with editorial staff, pesantren, Al-Muttaqien, also from Radar Kediri and Stain Kediri. This project held on the three institution are collaborated to introduce the partnership between the researcher, civil society, and the economic society. The result of this research shows that during preparation phase of construction materials santri stood up for capitalism but still based on consideration of news quality and values. Santri distributed its construction weekly, to Middle-Class city readers. By citizen journalism santri made the construction about radicalism at pesantren formed by means of negative image messages about pesantren, which extended through construction of text and selection of news sources. This influenced by ideological factor and journalists closeness to police and intelligent sources. Confirmation phase occurred when Al-Muttaqien sent a protest letter to santri into the social media, which caused readers interaction.